A study of Correlation Between motor Component of GCS score on Admission and Glasgow Outcome scale Score at Discharge in head injured Patients who underwent Surgical intervention (Bangladesh Medical Journal, 2014)
The aim of this study was to establish a correlation between the motor component of Glasgow Coma Scale (GCS) score on admission and Glasgow outcome scale (GCS) score at discharge (on 10th post-operative day) who underwent surgical intervention in head injured patients. This cross sectional study was carried out at the department of neurosurgery, BSMMU from November; 2005 to May, 2007 on head injured patients who underwent surgical intervention. A total of (35 patients with their age ranged from 5 yrs to 50 yrs who came within 3 days after head injury were included in this study. The patients were examined and the motor component of GCS score on admission and GOS at discharge (on 10th postoperative day) were recorded. Data were collected with the help of a structured questionnaire and face-to-face interview with the attendants of the patients. All relevant data were compiled manually in a master data sheet and then organized by scientific calculator. Best motor response and GOS score exhibit a linear relationship (r = 0.372, p = 0.028) indicating that higher the best motor response on admission higher is the GOS score at discharge (on 10th post-operative day). DOI: http://dx.doi.org/10.3329/bmj.v40i2.18509 Bangladesh Medical Journal 2011 Vol.40(2): 41-46